Respon Masyarakat Perampuan Terhadap Dakwah Jamaah Tabligh di Desa Perampuan barat di Kecamatan Labuapi Lombok Barat - Moh. Zarkoni (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
The existence of da'wah is very urgent in Islam. Da'wah and Islam cannot be separated from each other. As is known, da'wah is an effort to invite, call and influence people to always adhere to the teachings of Allah in order to obtain happiness in life in this world and the hereafter. Islam is a universal religion, revealed as a blessing for the entire universe. But the grace it contains will not be felt without an effort to spread it, namely da'wah. Among the problems that the author raises in this research are: How is the da'wah material of the Tabligh Jama'ah in delivering da'wah messages at the Nurusshalihin Mosque in West Labuapi. This research method uses a type of qualitative approach that is descriptive . The location of the research is at the Nurusshalihin Mosque in West Labuapi. The data collection techniques used include: (1) observation (2) interviews (3) documentation. The validity and reliability techniques used consist of four criteria, namely: (1) degree of credibility, (2) transferability, (3) dependability, (4) certainty. The results and discussion of the research are based on the data obtained by the researcher, so the researcher can conclude that the da'wah material of Jama'ah Tabligh is creed, sharia, morals and is based on the Quran, sunnah, ijma' and qiyas. The delivery of the Da'wah messages of the Tabligh Jama'ah is effective. Because the community around the Nurusshalihin Mosque has achieved what is the goal of the Tabligh Jama'ah itself, such as the prosperity of the mosque, the surrounding community has practiced many of the sunnahs of the Prophet SAW.